ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL MATERI PERSAMAAN GARIS LURUS BERDASARKAN PROSEDUR NEWMAN - Nia Rahmawati; Nelly Fitriani; Indah Puspita Sari; Citra Megiana Pertiwi (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This study analyzes students' errors in doing exercises on the material of Straight-Line Equations (PGL) based on the Newman procedure. This research was conducted at one of the schools in Cianjur area, with the research subject of 12 students. The method used in this analysis is the qualitative descriptive method because it will describe the form of student errors. The data collection technique uses 5 test items. The questions were made according to the predetermined indicators of achievement of basic competencies. Furthermore, based on students' answers, the researcher analyzed the extent to the students' errors in solving PGL questions. The results showed that: (1) 50% had errors in reading problems, namely students were less careful; (2) 16.7% experienced errors in understanding the problem, namely not being able to understand (3) 66.7% experienced problem transformation errors, namely difficulties in making graphs from the instructions presented, and students did not correctly convert the information obtained into PGL graphs; (4) 50% experienced errors in process skills, namely students were not able to solve the problems and be careless in the calculation process; (5) 83.3% experienced writing errors/answer notation, namely incorrectly in writing negative signs, symbols, equals signs, not writing variables and conclusions.